Synergistic Apoptotic Effects of Tocotrienol Isomers and Acalypha wilkesiana on A549 and U87MG Cancer Cells - Ibrahim Babangida Abubakar,; Su-Wen Lim,; Hwei-San Loh, (Tropical Life Sciences Research, 2018)
Recent studies suggested that combined treatment approaches can be used to improve anticancer potency and circumvent the limitations of high-dose tocotrienols administration. Acalypha wilkesiana is a medicinal plant that has been used as an adjunct treatment for cancers in traditional medicine. Herein, the effects of single and combined treatments of ?-, ?- and ?-tocotrienols and ethyl acetate extract (9EA) of Acalypha wilkesiana on lung (A549) and brain (U87MG) cancer cells were investigated. ?- and ?-tocotrienols exhibited higher potent antiproliferative effects against A549 (12.1 ?g/ml and 13.6 ?g/ml) and U87MG cells (3.3 ?g/ml and 5.2 ?g/ml) compared to ?-tocotrienols (9.4 ?g/ml and 92.4 ?g/ml), respectively. Whereas, 9EA induced potent antiproliferative effects against U87MG cells only (2.0 ?g/ml). Combined treatments of tocotrienols and 9EA induced a synergistic growth inhibition with up to 8.4-fold reduction in potent doses of ?-, ?- and ?-tocotrienols on A549 cells. Apoptotic features were also evidenced on A549 cells receiving single and combined treatments. The synergism may greatly improve the therapeutic outcome for lung cancer. Kajian terbaru mencadangkan bahawa pendekatan gabungan rawatan boleh digunakan untuk meningkatkan potensi antikanser dan menghindari batasan pemberian tocotrienol dos tinggi. Acalypha wilkesiana adalah tumbuhan ubatan yang telah digunakan sebagai rawatan tambahan untuk kanser dalam perubatan tradisional. Di sini, kesan rawatan tunggal dan gabungan ?-, ?- dan ?-tocotrienols dan ekstrak etil asetat (9EA) daripada Acalypha wilkesiana pada paru-paru (A549) dan sel-sel kanser otak (U87MG) telah disiasat. ?- dan ?-tocotrienols menunjukkan kesan antiproliferatif yang lebih tinggi terhadap A549 (12.1 ?g/ml dan 13.6 ?g/ml) dan sel U87MG (3.3 ?g/ml dan 5.2 ?g/ml) berbanding ?-tocotrienols (9.4 ?g/ml), masing-masing. Sedangkan, 9EA merangsang kesan antiproliferatif yang kuat terhadap sel U87MG sahaja (2.0 ?g/ml). Rawatan terapi tocotrienols dan 9EA mencetuskan perencatan pertumbuhan sinergis sehingga pengurangan 8.4 kali ganda dalam dos yang kuat dari ?-, ?- dan ?-tocotrienols pada sel A549. Ciri-ciri apoptotic juga dibuktikan pada sel-sel A549 yang menerima rawatan tunggal dan gabungan. Sinergi ini boleh meningkatkan hasil terapeutik untuk kanser paru-paru.